Voraxor for Burndown and Residual Weed Control in Spring Fallow - Patrick W. Geier (Kansas Agricultural Experiment Station Research Reports, 2025)
The addition of Voraxor improved the burndown rate of all weed species evaluated compared to Zidua SC plus Enlist One, Boundary 6.5, or Matador-S alone early in the season. The 1.0 oz rate of Voraxor was as effective as the 1.4 oz rate for most species evaluated; only Palmer amaranth and green foxtail responded differently between Voraxor rates. Voraxor-containing treatments controlled Palmer amaranth, Russian thistle, and green foxtail 90% or more at 35 days after treatment, and kochia and puncturevine 84% to 100%.
Keywords: Efficacy; tank mixtures